"Oh Father, I Miss You So": The Emotional Burden of Fatherlessness among Male Adolescents - Aurelya, Shalwa; Wanda, Mutiara Oktavia; Br Bangun, Josie Madelinta; Mirza, Rina; Fadhilah, Cut Rafyqa (Journal of Educational, Health and Community Psychology, 2025)
The absence of a father figure, often termed fatherlessness, has profound implications for adolescent psychological development, particularly in the regulation and expression of emotion. This qualitative study aims to explore how fatherless adolescent boys regulate their emotions and derive meaning from their experiences of paternal absence. Three male participants aged 18–22 who had experienced fatherlessness due to death or parental separation were selected through purposive sampling. Data were collected using semi-structured interviews and analyzed using reflexive thematic analysis as proposed by Braun and Clarke. The analysis identified four core themes: (1) Negative Emotions Due to Father Absence, including sadness, social comparison, and emotional instability; (2) Emotion Regulation through Avoidance and Distraction, such as engaging in sports, digital entertainment, and isolation; (3) Emotional Expression and Maladaptive Coping, including substance use, aggression, and spiritual reflection; and (4) Meaning-Making and Identity Reconstruction, in which participants described increased independence, self-reliance, and the aspiration to be a source of pride for their remaining parent, typically the mother. The findings reveal that while fatherless adolescents exhibit emotional vulnerability, they also show potential for resilience and post-traumatic growth when supported by meaningful relationships and personal coping mechanisms. It is recommended that psychological interventions for fatherless youth include emotion-focused therapy, cognitive restructuring, and mentorship programs to foster positive male identity development and emotional well-being.